CD19 expression in pediatric patients with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia pre‐ and post‐treatment with blinatumomab. Issue 12 (14th September 2021) - Mejstrikova, Ester; Klinger, Matthias; Markovic, Ana; Zugmaier, Gerhard; Locatelli, Franco
Abstract: Blinatumomab is a BiTE ® (bispecific T‐cell engager) immuno‐oncology therapy, which has demonstrated significant activity in patients with relapsed or refractory B‐cell precursor acute lymphoblastic leukemia (R/R B‐ALL); however, a subset of patients relapse. Monitoring expression of cluster of differentiation (CD)19 in relapsed patients is critical to inform sequencing of subsequent therapies. The expression of CD19 in 59 pediatric patients with R/R B‐ALL was analyzed on the day of diagnosis of R/R B‐ALL and on days 15 and 29 of cycle 1 of blinatumomab. Most patients treated with one cycle of blinatumomab retained expression of CD19, and would therefore be eligible for subsequent anti‐CD19 CAR T‐cell therapy.